2015
DOI: 10.1021/ml500534c
|View full text |Cite
|
Sign up to set email alerts
|

Azolylthioacetamide: A Highly Promising Scaffold for the Development of Metallo-β-lactamase Inhibitors

Abstract: A new scaffold, azolylthioacetamide, was constructed and assayed against metallo-β-lactamases (MβLs). The obtained molecules specifically inhibited MβL ImiS, and 1c was found to be the most potent inhibitor, with a K i = 1.2 μM using imipenem as substrate. Structure-activity relationships reveal that the aromatic carboxyl improves inhibitory activity of the inhibitors, but the aliphatic carboxyl does not. Compounds 1c-d and 1h-i showed the best antibacterial activities against E. coli BL21(DE3) cells producing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
44
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(48 citation statements)
references
References 35 publications
2
44
1
Order By: Relevance
“…A few triazole–thione analogues with no amino group at the 4‐position were reported to be modest inhibitors of the IMP‐1 MBL or were shown to be inactive against the CcrA, ImiS, and L1 MBLs at 50 μ m . Other triazole–thione compounds with an alkylated sulfur atom have also been published more recently, and the structure of the complex formed by one of these compounds with VIM‐2 showed that the two zinc atoms were coordinated by the nitrogen atoms at the 1‐ and 2‐positions of the heterocycle …”
Section: Introductionmentioning
confidence: 99%
“…A few triazole–thione analogues with no amino group at the 4‐position were reported to be modest inhibitors of the IMP‐1 MBL or were shown to be inactive against the CcrA, ImiS, and L1 MBLs at 50 μ m . Other triazole–thione compounds with an alkylated sulfur atom have also been published more recently, and the structure of the complex formed by one of these compounds with VIM‐2 showed that the two zinc atoms were coordinated by the nitrogen atoms at the 1‐ and 2‐positions of the heterocycle …”
Section: Introductionmentioning
confidence: 99%
“…In this work, we synthesized a series of 2-triazolylthioacetamides as previously reported [25], tested their inhibitory activity against VIM-2, and evaluated their efficiency to restore antibacterial activity of cefazolin against bacteria expressing VIM-2. Further, the binding affinities of 2triazolylthioacetamides to VIM-2 were determined by isothermal titration calorimetry (ITC).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, several complexes of crystal structures of VIM-2 with small molecules have been reported [7,11,13].Recently, we found that azolylthioacetamides are the potent MβL inhibitors [23-26], these compounds showed broad-spectrum inhibition on CcrA [24], 24,26], ImiS [24][25][26], and L1 [24], as the representative of three subclasses enzymes, respectively. Further, we reported an aromatic carboxyl substituted azolylthioacetamide as an inhibitor of VIM-2, which provided the binding via the complex crystal structure of enzyme and inhibitor [27].In this work, we synthesized a series of 2-triazolylthioacetamides as previously reported [25], tested their inhibitory activity against VIM-2, and evaluated their efficiency to restore antibacterial activity of cefazolin against bacteria expressing VIM-2.Further, the binding affinities of 2-triazolylthioacetamides to VIM-2 were determined by isothermal titration calorimetry (ITC). Finally, the crystal structure of VIM-2 in complex with a 2-triazolylthioacetamide molecule was determined and the interaction between enzyme and inhibitor was explored by crystallographic studies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, several recent reports have described new strategies and scaffolds to advance of field of MBL inhibitor discovery. These include: (i) the design of mechanism-based inhibitors where the anionic azanide intermediate is well-stabilized, thus leading to prolonged residence times in the active sites of MBLs[36]; (ii) zinc-binding azolylthioacetamides which have been found to serve as (sub)micromolar inhibitors of CcrA, NDM-1, ImiS and L1[79,80]; (iii) natural product zinc chelators such as aspergillomarasmine A…”
mentioning
confidence: 99%